2021
DOI: 10.5334/aogh.3205
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment of a District-Wide Quality Improvement on Newborn Care Program in Rural Rwanda: A Mixed-Method Study

Abstract: Background: Neonatal mortality continues to be a global challenge, particularly in low-and middle-income countries. There is growing work to reduce mortality through improving quality of systems and care, but less is known about sustainability of improvements in the setting post initial implementation. We conducted a 12-month sustainability assessment of All Babies Count (ABC), a district-wide quality improvement project including mentoring and improvement collaborative designed to improve quality and reduce n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…High levels of staff turnover were problematic for collaboration, this may be a particular issue where those trained in QI or who have the highest QI capacities are the most likely to be promoted elsewhere [ 35 , 36 ]. For QI to be sustainable some level of stability in the team is needed [ 37 , 38 ], unless QIC becomes institutionalized and known by all staff.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of staff turnover were problematic for collaboration, this may be a particular issue where those trained in QI or who have the highest QI capacities are the most likely to be promoted elsewhere [ 35 , 36 ]. For QI to be sustainable some level of stability in the team is needed [ 37 , 38 ], unless QIC becomes institutionalized and known by all staff.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the authors discussed the challenges they faced and the resilience that was needed to overcome organizational, cultural, and resource constraints. Barriers to effective QI programs are common in virtually all settings, but especially in LMICs (27) given limited resources (12,13,37,43,54,56,64,76,83,94,95,121), competing priorities (49,93), natural disasters (90), ambiguous governance (12,13), political and social strife (40,42,44,67,74,76,104). A common challenge was a high turnover of nurses, healthcare staff, and QI team members, which made ongoing leadership directions and sustained changes di cult (28, 34,43,45,49,51,53,80,93,121,124) and led to loss of organizational memory and trust (15).…”
Section: Theme Iv: Resilience In Managing External Challengesmentioning
confidence: 99%
“…Such studies have found maintenance of workforce skills through ongoing training and mentoring opportunities, leadership buy-in and reviews of progress against improvement goals have sustained improvements in a range of antenatal care practices for periods between 1 and 5 years. 41 42 …”
Section: Introductionmentioning
confidence: 99%
“…This suggests that factors that commonly impede sustainment of care delivery change may not have been sufficiently addressed by the trial implementation support package39 and that specific sustainability strategies may be required to ensure achieved effect sizes are maintained 40. A limited number of studies have tested the effect of sustainability strategies in maintaining improvements in evidence-based interventions in maternity service settings,41 42 with none specific to alcohol care. Such studies have found maintenance of workforce skills through ongoing training and mentoring opportunities, leadership buy-in and reviews of progress against improvement goals have sustained improvements in a range of antenatal care practices for periods between 1 and 5 years 41 42…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation